Thermographic evaluation of hind paw skin temperature and functional recovery of locomotion after sciatic nerve crush in rats (Clinics, 2011)
INTRODUCTION: Peripheral nerves are often damaged by direct mechanical injury, diseases, and tumors. The peripheral nerve injuries that result from these conditions can lead to a partial or complete loss of motor, sensory, and autonomic functions, which in turn are related to changes in skin temperature, in the involved segments of the body. The aim of this study was to evaluate the changes in hind paw skin temperature after sciatic nerve crush in rats in an attempt to determine whether changes in skin temperature correlate with the functional recovery of locomotion. METHODS: Wistar rats were divided into three groups: control (n = 7), sham (n = 25), and crush (n = 25). All groups were subjected to thermographic, functional, and histological assessments. RESULTS: ΔT in the crush group was different from the control and sham groups at the 1st, 3rd and 7rd postoperative days (p